Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To find the derivative [tex]\( f'(a) \)[/tex] at the given number [tex]\( a \)[/tex], let's follow the detailed steps:
### Step 1: Define the function
The function given is:
[tex]\[ f(x) = \sqrt{3x + 1} \][/tex]
### Step 2: Find the derivative [tex]\( f'(x) \)[/tex]
To find the derivative, we use the chain rule. The chain rule states that if you have a composite function [tex]\( f(g(x)) \)[/tex], then the derivative [tex]\( f'(x) \)[/tex] is [tex]\( f'(g(x)) \cdot g'(x) \)[/tex].
Let [tex]\( u = 3x + 1 \)[/tex]. Then, [tex]\( f(x) = \sqrt{u} \)[/tex].
First, find the derivative of [tex]\( \sqrt{u} \)[/tex] with respect to [tex]\( u \)[/tex]:
[tex]\[ \frac{d}{du} (\sqrt{u}) = \frac{1}{2\sqrt{u}} \][/tex]
Next, find the derivative of [tex]\( u = 3x + 1 \)[/tex] with respect to [tex]\( x \)[/tex]:
[tex]\[ \frac{du}{dx} = 3 \][/tex]
Now, apply the chain rule:
[tex]\[ f'(x) = \frac{d}{dx} (\sqrt{3x + 1}) = \frac{d}{du} (\sqrt{u}) \cdot \frac{du}{dx} = \frac{1}{2\sqrt{3x + 1}} \cdot 3 = \frac{3}{2\sqrt{3x + 1}} \][/tex]
So, the derivative of [tex]\( f(x) \)[/tex] is:
[tex]\[ f'(x) = \frac{3}{2\sqrt{3x + 1}} \][/tex]
### Step 3: Evaluate the derivative at [tex]\( x = a \)[/tex]
Given [tex]\( a = 5 \)[/tex], we need to evaluate [tex]\( f'(5) \)[/tex].
Substitute [tex]\( x = 5 \)[/tex] into the derivative:
[tex]\[ f'(5) = \frac{3}{2\sqrt{3(5) + 1}} = \frac{3}{2\sqrt{15 + 1}} = \frac{3}{2\sqrt{16}} = \frac{3}{2 \cdot 4} = \frac{3}{8} \][/tex]
### Conclusion
The derivative of the function [tex]\( f(x) = \sqrt{3x + 1} \)[/tex] at [tex]\( a = 5 \)[/tex] is:
[tex]\[ f'(5) = \frac{3}{8} \][/tex]
This gives us the exact value of the derivative at the specified point.
### Step 1: Define the function
The function given is:
[tex]\[ f(x) = \sqrt{3x + 1} \][/tex]
### Step 2: Find the derivative [tex]\( f'(x) \)[/tex]
To find the derivative, we use the chain rule. The chain rule states that if you have a composite function [tex]\( f(g(x)) \)[/tex], then the derivative [tex]\( f'(x) \)[/tex] is [tex]\( f'(g(x)) \cdot g'(x) \)[/tex].
Let [tex]\( u = 3x + 1 \)[/tex]. Then, [tex]\( f(x) = \sqrt{u} \)[/tex].
First, find the derivative of [tex]\( \sqrt{u} \)[/tex] with respect to [tex]\( u \)[/tex]:
[tex]\[ \frac{d}{du} (\sqrt{u}) = \frac{1}{2\sqrt{u}} \][/tex]
Next, find the derivative of [tex]\( u = 3x + 1 \)[/tex] with respect to [tex]\( x \)[/tex]:
[tex]\[ \frac{du}{dx} = 3 \][/tex]
Now, apply the chain rule:
[tex]\[ f'(x) = \frac{d}{dx} (\sqrt{3x + 1}) = \frac{d}{du} (\sqrt{u}) \cdot \frac{du}{dx} = \frac{1}{2\sqrt{3x + 1}} \cdot 3 = \frac{3}{2\sqrt{3x + 1}} \][/tex]
So, the derivative of [tex]\( f(x) \)[/tex] is:
[tex]\[ f'(x) = \frac{3}{2\sqrt{3x + 1}} \][/tex]
### Step 3: Evaluate the derivative at [tex]\( x = a \)[/tex]
Given [tex]\( a = 5 \)[/tex], we need to evaluate [tex]\( f'(5) \)[/tex].
Substitute [tex]\( x = 5 \)[/tex] into the derivative:
[tex]\[ f'(5) = \frac{3}{2\sqrt{3(5) + 1}} = \frac{3}{2\sqrt{15 + 1}} = \frac{3}{2\sqrt{16}} = \frac{3}{2 \cdot 4} = \frac{3}{8} \][/tex]
### Conclusion
The derivative of the function [tex]\( f(x) = \sqrt{3x + 1} \)[/tex] at [tex]\( a = 5 \)[/tex] is:
[tex]\[ f'(5) = \frac{3}{8} \][/tex]
This gives us the exact value of the derivative at the specified point.
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.